Evaluation of the immune status against measles, mumps, and rubella in adult allogeneic hematopoietic stem cell transplantation recipients. Issue 2 (March 2015) - Kawamura, Koji; Yamazaki, Rie; Akahoshi, Yu; Nakano, Hirofumi; Ugai, Tomotaka; Wada, Hidenori; Yamasaki, Ryoko; Ishihara, Yuko; Sakamoto, Kana; Ashizawa, Masahiro; Sato, Miki; Terasako-Saito, Kiriko; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Previous studies have shown that most patients lose immunity to measles, mumps, and rubella (MMR) during long-term follow-up after allogeneic hematopoietic stem cell transplantation (HSCT), and immunizations against them have been investigated. However, these previous studies mainly targeted pediatric patients and information in adult patients is still insufficient. Methods We evaluated the immunity to MMR in 45 adult allogeneic HSCT patients. None of these patients received vaccination after HSCT. Results The seropositive rates at six years after allogeneic HSCT were estimated to be less than 44% for measles, less than 10% for mumps, and less than 36% for rubella. Thirteen of the 16 female patients who were 16–39 years old were negative or equivocal for rubella. Patients who developed grade II–IV acute graft-versus-host disease tended to become seronegative for measles and rubella at two years after HSCT, although the difference was not statistically significant. Conclusions This study showed that most adult patients lost immunity to MMR after allogeneic HSCT. Although we did not evaluate the safety and efficacy of vaccination in this study, most HSCT guidelines recommend vaccination for HSCT recipients without active chronic graft-versus-host disease or ongoing immunosuppressive therapy at 24 months after HSCT. Immunization against rubella is especially important for female patients of reproductive age. Further studies will be necessary to evaluate the effect of vaccination on the antibody response in adult allogeneic HSCT recipients.